Clinical and Pharmaceutical Solutions through Analysis (CPSA BRASIL 2015): on the way to innovation – pharmaceutical/analytical technology, regulation and knowledge management. (December 2015) - Needham, Shane; Yates, Nathan; Barrientos, Rafael; Steel, Martin; Lee, Mike
Clinical and Pharmaceutical Solutions through Analysis, São Paulo, Brazil, 3–5 August 2015 The 2nd Annual Symposium on Clinical and Pharmaceutical Solutions through Analysis was held on 3–5 August 2015 at Club Transatlântico, São Paulo, Brazil. This annual meeting began in 2014 and was the first industry-led event in Brazil to focus on the specific needs of industry researchers while bringing together technology and regulators. The goal of CPSA is to provide an in-depth review of innovative technology and industry practices through open discussion of industry-related issues and needs. Education and specialized training are the foundation of all CPSA events. As the industry has evolved so has CPSA. The CPSA annual meeting thrived with high quality scientific content, open interaction from industry opinion leaders and a collegial environment.